CORRELATION OF BLOOD SUGAR WHEN ENTER THE HOSPITAL WITH INCIDENCE OF PNEUMONIA ON INPATIENTS COVID-19 AT THE JAKARTA HOSPITAL IN THE PERIOD MARCH – DECEMBER 2020 AND THE REVIEW ACCORDING TO THE ISLAMIC POINT OF VIEW - Dwiky Anantya Vergian; Syahrizal Syahrizal; Ali Ma'sum (Junior Medical Journal, 2022)
The lungs are the ones that have large amounts of angiotensin converting enzyme 2 (ACE2) receptors, so there are symptoms in the lungs due to infection with the SARS-CoV-2 virus. Radiological results from COVID-19 generally show a picture of pneumonia. Chronic disease diabetes mellitus is one of the diseases that is a major risk factor for COVID-19. This is because diabetics experience hyperglycemia, impaired immune function, vascular complications and comorbidities. In addition, diabetes mellitus can also guarantee the condition of COVID-19 due to a dysfunctional response of pro-inflammatory cytokines in patients with diabetes mellitus. Thus, COVID-19 patients with diabetes had a wider distribution of bilateral lung lesions compared to other groups. The data used in this study used secondary data with quantitative data types. The source of the research data was taken from the data of patients diagnosed with COVID-19 at the Jakarta Hospital for the March - December 2020 period who met the research inclusion criteria. It was found that in COVID-19 patients with diabetes, the majority had pneumonia as many as 25 patients (69.64%) and in COVID-19 patients without diabetes, the majority had pneumonia as many as 79 patients (51.3%). By referring to the results of statistical analysis, the resulting p-value is 0.075 which proves that there is no significant relationship between blood sugar and the incidence of pneumonia in COVID-19 patients at the Jakarta Hospital for the period March - December 2020.